Cyst in the fetal pelvis: An integrative review (Research, Society and Development, 2023)
Introduction: The cyst in the fetal pelvis is a condition that can cause concern and anxiety in parents, since it can be identified during ultrasound examinations performed during pregnancy. This anomalous finding in the pelvic region of the fetus may raise questions about the impact on the baby's health and potential complications during intrauterine development. Objective: To provide a comprehensive and up-to-date analysis of the cyst in the fetal pelvis, addressing its definition, causes, diagnosis and possible clinical consequences. Methodology: This study follows the guidelines of an integrative review, adopting a descriptive and qualitative approach. Results and Discussion: The evidence selection process prioritized the most comprehensive and up-to-date materials on the subject of fetal pelvic cyst. It is important to emphasize that, although complications are possible, not all cases of cyst in the fetal pelvis will result in serious clinical consequences. Most ovarian cysts in fetuses tend to regress spontaneously, and adequate medical follow-up is essential to monitor the development and evolution of the cysts. Conclusion: In short, the importance of up-to-date knowledge about fetal pelvic cysts is evident, including its definition, causes, diagnosis and possible clinical consequences. The in-depth understanding of this condition allows for an appropriate approach, offering peace of mind to parents and ensuring the health and well-being of the fetus. As fetal medicine advances, it is expected that new studies and technological advances will continue to improve our knowledge and clinical management of these cysts, providing better patient outcomes.